2016
DOI: 10.1021/acs.chemrev.5b00577
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Interactions by Quantum Monte Carlo

Abstract: Quantum Monte Carlo (QMC) is a family of stochastic methods for solving quantum many-body problems such as the stationary Schrödinger equation. The review introduces basic notions of electronic structure QMC based on random walks in real space as well as its advances and adaptations to systems with noncovalent interactions. Specific issues such as fixed-node error cancellation, construction of trial wave functions, and efficiency considerations that allow for benchmark quality QMC energy differences are descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
158
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(164 citation statements)
references
References 269 publications
3
158
0
Order By: Relevance
“…Monte Carlo (QMC), [44][45][46] and density functional theory (DFT). [47][48][49][50] Each method offers different strengths in computational accuracy, expense, and model complexity.…”
Section: Introduction To Theoretical Methodsmentioning
confidence: 99%
“…Monte Carlo (QMC), [44][45][46] and density functional theory (DFT). [47][48][49][50] Each method offers different strengths in computational accuracy, expense, and model complexity.…”
Section: Introduction To Theoretical Methodsmentioning
confidence: 99%
“…24 CCSD(T) can be applied to complexes having up to around 35 heavy atoms, while MP2.5 can handle systems up to twice the size. Unfortunately, however, no reference method of comparable quality is currently available for use with periodic models, with the exception of the stochastic quantum Monte Carlo method, 22,26,27 that embody exceeding computational demands.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Previous studies have shown that diffusion quantum Monte Carlo (DMC) can provide accurate energies for noncovalent interactions systems. [26][27][28][29][30] DMC can also produce an accurate description of the phase diagram of materials under pressure. [31][32][33] In general, QMC-based methods are faster than the most accurate post-Hartree-Fock schemes for large number of particles N. The computational cost of QMC methods scales usually as N 3 -N 4 depending on the method.…”
Section: Introductionmentioning
confidence: 99%